2020
DOI: 10.1111/jcmm.14884
|View full text |Cite
|
Sign up to set email alerts
|

Verbascoside inhibits progression of glioblastoma cells by promoting Let‐7g‐5p and down‐regulating HMGA2 via Wnt/beta‐catenin signalling blockade

Abstract: Glioblastoma (GBM) continues to show a poor prognosis despite advances in diagnostic and therapeutic approaches. The discovery of reliable prognostic indicators may significantly improve treatment outcome of GBM. In this study, we aimed to explore the function of verbascoside (VB) in GBM and its effects on GBM cell biological processes via let‐7g‐5p and HMGA2. Differentially expressed GBM‐related microRNAs (miRNAs) were initially screened. Different concentrations of VB were applied to U87 and U251 GBM cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 39 publications
(79 reference statements)
0
19
0
Order By: Relevance
“…Accordingly, VB has been demonstrated to repress GBM cell viability, invasion, migration, and tumor growth while promoting GBM cell apoptosis by increasing let-7g-5p expression and inhibiting high-mobility group (HMG)A2 expression. 28 Our study findings demonstrated that miR-7-5p was poorly expressed in GBM, and the administration with VB induced the secretion of exosomal miR-7-5p, which could consequently exercise an inhibitory effect on GBM cell proliferation, invasion, migration, and vessel-like tube formation. Currently, miR-7-5p has been highlighted to function as a tumor suppressor involved in various cancers, including GBM.…”
Section: Discussionmentioning
confidence: 57%
“…Accordingly, VB has been demonstrated to repress GBM cell viability, invasion, migration, and tumor growth while promoting GBM cell apoptosis by increasing let-7g-5p expression and inhibiting high-mobility group (HMG)A2 expression. 28 Our study findings demonstrated that miR-7-5p was poorly expressed in GBM, and the administration with VB induced the secretion of exosomal miR-7-5p, which could consequently exercise an inhibitory effect on GBM cell proliferation, invasion, migration, and vessel-like tube formation. Currently, miR-7-5p has been highlighted to function as a tumor suppressor involved in various cancers, including GBM.…”
Section: Discussionmentioning
confidence: 57%
“…HMGA2 is suppressed by let-7g-5p and down-regulation of HMGA2 expression can promote GBM tumor cell apoptosis and inhibit their invasion, indicating that HMGA2 is a potential novel target gene in GBM. 36 In addition, HMGA2 can be targeted by miR-370-3p , which inhibits glioma cell growth and invasion 37 and is, therefore, a potential target for glioma therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have validated that targeting HMGA2 in GBM may be therapeutically beneficial. High expression of HMGA2 in GBM has been confirmed to promote GBM cell viability, invasion, migration, stemness and tumor growth, inhibit cell apoptosis and autophagy ( 37 , 38 ), and be involved in the double-strand break repair pathway ( 39 ). LINC00336, despite the lack of any study in GBM, has been identified to be significantly correlated with renal cell carcinoma OS ( 40 ), and its overexpression may promote lung cancer cell growth, colony formation, and tumor formation, and inhibit ferroptosis ( 41 ).…”
Section: Discussionmentioning
confidence: 99%